The aerotaxis of Dictyostelium discoideum is independent of mitochondria, nitric oxide and oxidative stress - Hirose, Satomi; Hesnard, Julie; Ghazi, Nasser; Roussel, Damien; Voituron, Yann; Cochet-Escartin, Oliver; Rieu, Jean-Paul; Anjard, Christophe; Funamoto, Kenichi (Frontiers in Cell and Developmental Biology, 2023)
Spatial and temporal variations of oxygen environments affect the behaviors of various cells and are involved in physiological and pathological events. Our previous studies with Dictyostelium discoideum as a model of cell motility have demonstrated that aerotaxis toward an oxygen-rich region occurs below 2% O2. However, while the aerotaxis of Dictyostelium seems to be an effective strategy to search for what is essential for survival, the mechanism underlying this phenomenon is still largely unclear. One hypothesis is that an oxygen concentration gradient generates a secondary oxidative stress gradient that would direct cell migration towards higher oxygen concentration. Such mechanism was inferred but not fully demonstrated to explain the aerotaxis of human tumor cells. Here, we investigated the role on aerotaxis of flavohemoglobins, proteins that can both act as potential oxygen sensors and modulators of nitric oxide and oxidative stress. The migratory behaviors of Dictyostelium cells were observed under both self-generated and imposed oxygen gradients. Furthermore, their changes by chemicals generating or preventing oxidative stress were tested. The trajectories of the cells were then analyzed through time-lapse phase-contrast microscopic images. The results indicate that both oxidative and nitrosative stresses are not involved in the aerotaxis of Dictyostelium but cause cytotoxic effects that are enhanced upon hypoxia.